Reimagining Microbially Induced Concrete Deterioration: A Novel Approach Through Coupled Confocal Laser Scanning Microscope–Avizo Three-Dimensional Modeling of Biofilms - Mingyue Ma; Guangda Yu; Zhen Xu; Jun Hu; Ziyuan Ji; Zihan Yang; Yumeng Sun; Yeqian Zhen; Jingya Zhou (Microorganisms, 2025)
Microbially induced concrete deterioration (MID) poses a significant and urgent challenge to urban sewerage systems globally, particularly in tropical coastal regions. Despite the acknowledged importance of biofilms in MICC, limited research on sewer pipe biofilms has hindered a comprehensive understanding of their deterioration mechanisms. To overcome this limitation, our research employed multiple staining techniques and digital volume correlation (DVC) technology, creating a new method to analyze the microstructure of biofilms, precisely identify the components of EPSs, and quantitatively examine MID mechanisms from a microscopic viewpoint. Our results revealed that the biofilm on concrete surfaces regulates the types of amino acids, thereby creating an environment conducive to microbial aggregate survival. Additionally, salinity significantly influences biofilm component distribution, while proteins play a pivotal role in biofilm mechanical stability. Notably, a high salinity fosters microbial migration within the biofilm, exacerbating deterioration. Through this multidimensional inquiry, our study established an advanced echelon of comprehension concerning the intricate mechanisms underpinning MICC. Meanwhile, by peering into the biofilms and elucidating their interplay with concrete, our findings offer profound insights, which can aid in devising strategies to counter urban sewer system deterioration.